Analisis Faktor-Faktor yang Mempengaruhi Perilaku Etis dalam Bisnis - Devina Shava Amalia; Ataina Rusyda Fauziyah; Tries Ellia Sandari (Jurnal Mutiara Ilmu Akuntansi, 2025)
Business ethics here does not only talk about human behavior towards nature but talks about the relationship between all the life of the universe, between humans and humans who have an impact on nature, and between humans and other creatures or with nature as a whole, including political and economic policies that relate or have a direct impact or not with nature. The method used in this research is descriptive qualitative because it tries to explain without making comparisons or connecting with other variables. It was found that business ethics is a pillar that is not only important for sustainability but also for growth and competitiveness. Consistently applied ethical principles can create long-term value and strengthen the company's relationship with all related parties.